SUNDARBAN MANGROVE FOREST OF THE LOWLAND OF SOUTHWESTERN BANGLADESH AND ITS HYDROGEO-ENVIRONMENTAL ASPECTS - M. Q. Hassan; K. R. Chowdhury (International Association of Lowland Technology, 2004)
The paper presents the Sundarban Mangrove Forest and its hydro-environmental aspects in particular. The Sundarban Forest is covered by numerous distributaries of the Ganges delta along the coastal belt of the Bay of Bengal of southwest lowland area. The lithological distribution of surface area is of Geological Quarternary Age.These are clay,mud, silt, medium to fine sand and small patches of shell fragments In the beach area. Brief investigation of channel/ stream / river waters which indicated that the pH values varied from 7.5 to 8.4 and the recorded electrical conductivity (EC) ranges from 7,920 to 19,400 us/cm, and others ionic concentrations are also found in higher condition. The Sundarban Mangrove Forest frequently become of severe cyclones, tidal fooding and storm surges. The present study can help in the future planning and development of the lowland area of the Sundarban Mangrove Forest.